Self-medication practices among customers at non-pharmacy outlets during COVID-19 pandemic in Indonesia - Wibowo, Yosi Irawati; Kusuma Yana, I Gusti Agung Ari; Puspa Sari, Gusti Ayu Putu Laksmi; Sunderland, Bruce; Setiadi, Adji Prayitno (Intelektual Pustaka Media Utama, 2024)
A cross-sectional study was performed to describe self-medication practices of customers at kiosks and minimarkets in District X, Indonesia, during COVID-19 pandemic in 2021. A sample of 98 customers from 67 kiosks, and 100 customers from 52 minimarkets were interviewed using a validated questionnaire. Descriptive statistics were used to summarise the findings. Most drugs purchased at kiosks and minimarkets were general sales drugs, i.e., analgesic-antipyretic (64.3% versus 46.0%); however, prescription drug sales were reported (3.1% vs 3.0%, respectively). Kiosk and minimarket customers purchased medications mainly based on the recommendations of non-health workers (69.4% vs. 34.0%, respectively), or electronic media (36.7% vs. 43.0%, respectively). The reasons to choose kiosks or minimarkets included accessibility, personal preferences, and service quality. Most kiosk/minimarket customers had knowledge on the drug brand names and indications, but only some knew the composition (8.16% vs. 29.0%, respectively) or side effects (9.18% vs. 35.0%, respectively). These findings indicated limited quality assurance on self-medication practices at non-pharmacy outlets.